Impact Of Oxygenated Water On The Acceleration Of Pulse Rate Reduction After Physical Activity - Putri, Wahyu Setia Kuscahyaning; Aliriad, Hilmy (Physical Activity Journal (PAJU), 2023)
This study examines the effect of drinking water with oxygen levels to decrease the pulse rate after physical activity in students of Physical Education Health and Recreation. The research method used is experimental research with Pretest-Posttest Control Group Design. Two groups were formed: a control group and an experimental group of 20 UNUGIRI Health and Recreation Physical Education Study Program students. Sampling is done randomly (Random Sampling). The pulse rate is measured before and after running for 20 minutes. The results of the analysis showed a significant difference between the provision of oxygenated drinking water (experimental group) and ordinary drinking water (control group) on the acceleration of pulse rate reduction after running activities. The significance value obtained was 0.057, indicating a significant difference between the two groups. The average pulse of the experimental group was 89.44, while the average pulse of the control group was 98.33. The administration of drinking water with an oxygen content has a positive effect on the decrease in the pulse rate after physical exertion. Subjects who consumed oxygenated drinking water after a 20-minute run had a faster pulse rate decrease than those who consumed only plain water. The conclusion of this study shows that the provision of oxygenated drinking water positively affects the decrease in pulse rate after physical activity in health and Recreation physical education students. Oxygenated drinking water can be an effective alternative to accelerate pulse recovery after intense physical exertion. This research provides a better understanding of the benefits of oxygenated drinking water in maintaining health and accelerating physical recovery after sports activities